No association between vitamin D and β‐cell autoimmunity in Finnish and Estonian children. Issue 8 (November 2014) - Reinert‐Hartwall, L.; Honkanen, J.; Härkönen, T.; Ilonen, J.; Simell, O.; Peet, A.; Tillmann, V.; Lamberg‐Allardt, C.; Virtanen, S. M.; Knip, M.; Vaarala, O.; The DIABIMMUNE Study Group
Abstract Background Vitamin D has immunomodulatory properties, such as regulation of FOXP3 expression and regulatory T‐cell activity. Our aim was to investigate whether plasma 25‐hydroxyvitamin D [25(OH)D] concentrations associate with the development of β‐cell autoimmunity and the transcriptional activity of FOXP3 or vitamin D3 convertase gene (CYP27B1) in CD4+ memory T cells. Methods We studied 83 Finnish and 32 Estonian children participating in the DIABIMMUNE and DIPP studies. Twenty‐nine Finnish and six Estonian children tested positive for at least one diabetes‐associated autoantibody. The plasma concentrations of 25(OH)D and 1, 25(OH)2D were analysed with an enzyme immunoassay. Gene expression of FOXP3 and CYP27B1 in the isolated CD4+ memory T cells was studied with reverse transcription quantitative polymerase chain reaction. Results Vitamin D status did not differ between subjects positive and negative for β‐cell autoantibodies. Finnish children had higher vitamin D status than Estonian children (p < 0.001). FOXP3 expression was higher in Estonian CD4+ memory T‐cell samples than in Finnish samples (p < 0.01) even when including in both groups only children with serum 25(OH)D concentrations in the range of 50–80 nmol/L (p < 0.001). Conclusions These findings do not support a crucial role of circulating 25(OH)D as a regulator of β‐cell autoimmunity or FOXP3 expression. Copyright © 2014 John Wiley & Sons, Ltd.